Phenotypic alteration of low-density granulocytes in people with pulmonary post-acute sequelae of SARS-CoV-2 infection - Dean, Logan S.; Devendra, Gehan; Jiyarom, Boonyanudh; Subia, Natalie; Tallquist, Michelle D.; Nerurkar, Vivek R.; Chang, Sandra P.; Chow, Dominic C.; Shikuma, Cecilia M.; Park, Juwon (Frontiers in Immunology, 2022)
Low-density granulocytes (LDGs) are a distinct subset of neutrophils whose increased abundance is associated with the severity of COVID-19. However, the long-term effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on LDG levels and phenotypic alteration remain unexplored. Using participants naïve to SARS-CoV-2 (NP), infected with SARS-CoV-2 with no residual symptoms (NRS), and infected with SARS-CoV-2 with chronic pulmonary symptoms (PPASC), we compared LDG levels and their phenotype by measuring the expression of markers for activation, maturation, and neutrophil extracellular trap (NET) formation using flow cytometry. The number of LDGs was significantly elevated in PPASC compared to NP. Individuals infected with SARS-CoV-2 (NRS and PPASC) demonstrated increased CD10+ and CD16hi subset counts of LDGs compared to NP group. Further characterization of LDGs demonstrated that LDGs from PPASC displayed higher NET forming ability and aggregation with platelets compared to LDGs from NP and NRS. Our data demonstrates that mature neutrophils with a heightened activation phenotype remain in circulation long after initial SARS-CoV-2 infection. Persistent elevation of markers for neutrophil activation and NET formation on LDGs, as well as an enhanced proclivity for platelet-neutrophil aggregation (PNA) formation in individuals with PPASC may be associated with the development of long-term pulmonary sequelae.